Innovations in cavity ringdown spectroscopy - Vallance, C (2005)
Cavity ringdown spectroscopy, based on the decay of light intensity within a high finesse optical cavity, is one of the most sensitive and versatile spectroscopic absorption techniques currently available. This Perspective examines some of the growing number of novel variations on the standard technique and evaluates their potential applications in spectroscopy and chemical/biological sensing. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique 2005.